Very high energy gamma rays from the composite SNR G0.9+0.1 - Funk, Stefan; et al. (Astronomy & Astrophysics, 2005)
Very high energy (> 100 GeV) gamma-ray emission has been detected for the first time from the composite supernova remnant G0.9+ 0.1 using the HESS instrument. The source is detected with a significance of approximate to 13sigma, and a photon flux above 200 GeV of ( 5.7 +/- 0.7(stat) +/- 1.2(sys)) x 10(-12) cm(-2) s(-1), making it one of the weakest sources ever detected at TeV energies. The photon spectrum is compatible with a power law ( dN/dE proportional to E-Gamma) with photon index Gamma = 2.40 +/- 0.11(stat) +/- 0.20(sys). The gamma-ray emission appears to originate in the plerionic core of the remnant, rather than the shell, and can be plausibly explained as inverse Compton scattering of relativistic electrons.
CRIS-Team WoS Importer:2020-01-15